A comparative study of early vs. delayed laparoscopic cholecystectomy in acute cholecystitis - Yadav, RP; Adhikary, S; Agrawal, CS; Bhattarai, B; Gupta, RK; Ghimire, A (Kathmandu University Medical Journal, 2009)
Aims and Objectives: To compare the outcome in early vs. delayed laparoscopic cholecystectomy in terms of frequency of intra-operative and postoperative complications and to determine the rate and reasons for conversion. Materials and methods: A prospective randomized clinical trial was performed in the Department of Surgery at BP Koirala Institute of Health Sciences from February 2003 to June 2004 in all patients with the diagnosis of acute calculus cholecystitis. Results: Out of 145 cases, 50 cases were included in our study where 12 (24%) patients were males and 38 (76%) were females (M:F=1:3.16). The mean (SD) age of patients in early and delayed groups were 42.68 yrs. (14.18) and 40.26 yrs. (11.62) respectively. The mean (SD) duration of symptoms in early successful and converted groups were 109.24 hrs. (43.66) and 132 hrs. (49.96) respectively and the mean (SD) duration of symptoms in delayed successful and converted groups were 15.36 months (13.88) and 41 months (40.73) respectively. In early group, 17 (68%) patients had total leukocyte count more than 10,000/cmm and they had ultrasound findings suggestive of acute cholecystitis. Out of 25 patients in early group, seven had jaundice and ten had deranged liver function in the preoperative period. In early group 4 (16%) patients; and in delayed group 3 (12%) had to be converted to open cholecystectomy (P=1.00). In early group 10 (40%) and in delayed 5 (20 %) cases had intra-operative complications (P=0.122). The total hospital stay was longer in the delayed group. The postoperative hospital stay in early and delayed converted groups were higher than early and delayed successful group (P=0.081, P=0.082). Conclusion: Both early and delayed laparoscopic cholecystectomy is possible and safe in the treatment of acute cholecystitis. Key words: Acute cholecystitis, Laparoscopic cholecystectomy, Conversion doi: 10.3126/kumj.v7i1.1759       Kathmandu University Medical Journal (2009), Vol. 7, No. 1, Issue 25, 16-20